2020
DOI: 10.1001/jamanetworkopen.2020.8243
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Air Pollution and Heat Exposure With Preterm Birth, Low Birth Weight, and Stillbirth in the US

Abstract: IMPORTANCE Knowledge of whether serious adverse pregnancy outcomes are associated with increasingly widespread effects of climate change in the US would be crucial for the obstetrical medical community and for women and families across the country.OBJECTIVE To investigate prenatal exposure to fine particulate matter (PM 2.5 ), ozone, and heat, and the association of these factors with preterm birth, low birth weight, and stillbirth. EVIDENCE REVIEWThis systematic review involved a comprehensive search for prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
364
4
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 543 publications
(420 citation statements)
references
References 77 publications
6
364
4
6
Order By: Relevance
“…Substantial reductions in air pollution have also been reported following COVID-19 mitigation measures, 34 including in the Netherlands. 35 Given the recognised increased risk of delivering preterm when exposed to air pollution, 36 this finding could explain part of the observed reductions. Because a large minority of preterm births are induced, usually for maternal or fetal health concerns, changes in obstetric practice or care-seeking behaviour of pregnant women might also have contributed.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial reductions in air pollution have also been reported following COVID-19 mitigation measures, 34 including in the Netherlands. 35 Given the recognised increased risk of delivering preterm when exposed to air pollution, 36 this finding could explain part of the observed reductions. Because a large minority of preterm births are induced, usually for maternal or fetal health concerns, changes in obstetric practice or care-seeking behaviour of pregnant women might also have contributed.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that offspring of women exposed to an extreme heat event with high levels of fine PM, had 1.59 (95% CI 0.94, 2.71) times the odds of having perimembranous VSD compared to women exposed to an extreme heat event with low exposure to fine PM [ 26 ]. Bekkar et al conducted a systematic review on air pollution and heat exposure on adverse pregnancy outcomes, such as preterm birth, stillbirth, and low birth weight [ 28 ]. Although the authors did not conduct a meta-analysis due to heterogeneity of study populations across geographic locations, 49 of the 58 (84%) articles that focused on air pollutants (PM and ozone) and 9 of the 10 articles that focused on heat showed significant direct associations with an adverse pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women and their fetuses are among the population most at-risk of these health harms, especially those resulting from extreme temperatures, poor air quality, food related infections, as well as mental health impacts. Exposure to air pollution and extreme heat both create elevated risk of serious obstetrical outcomes including preterm birth, low birthweight, and stillbirth [ 9 , 10 , 11 ]. Moreover, climate change is creating unprecedented exposures to extreme temperatures, smoke from wildfire, and other forms of air pollution in an expanding range of geographic locations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the harmful impacts of climate change and air pollution on pregnant women and their fetuses are well-established [ 7 , 9 , 10 , 11 , 12 ], little research has been conducted to assess pregnant women’s understanding of their and their fetuses’ health risks resulting from climate change. Moreover, to the best of our knowledge, no educational interventions have been tested.…”
Section: Introductionmentioning
confidence: 99%